Method for fixing harmonic injection share of utility or consumer or both at the point of energy metering. Issue 16 (29th June 2018) - Jaiswal, Supriya; Ballal, Makarand S
Abstract : This study presents a method to establish the harmonic injection responsibility of either utility or consumer or both at the energy metering point. The method involves voltage and current harmonic components extraction using fast discrete stockwell transform (FDST). FDST overcomes the limitations of fast Fourier transform (FFT) and thus gives more accurate magnitude and phase angle information of harmonic components irrespective of noise effect. These harmonic components are utilised in phasor analysis to derive harmonic indices which arbitrates the responsible source for harmonic injection at the metering point. Energy billing is proposed based on evaluation of percentage harmonic injection responsibility which eradicates the drawback of conventional billing method. Several experimental cases are presented in order to validate the reliability, accuracy and effectiveness of the proposed technique for different supply and loading conditions. The proposed method is implemented over LabVIEW to show its feasibility in real‐time scenario. The proposed energy billing scheme can be implemented in the existing energy meters and harmonic contribution share is easily attainable without any prior knowledge of network parameters.